The role of PAR2 in regulating MIF release in house dust mite-induced atopic dermatitis - Zhou, Lingxuan; Zhang, Guohong; Zhang, Kai; Rao, Ziyan; Tang, Zhanli; Wang, Yang; Zhao, Jiahui (Frontiers in Immunology, 2024)
Atopic dermatitis (AD) is a chronic disease characterized by relapsed eczema and intractable itch, and is often triggered by house dust mites (HDM). PAR2 is a G-protein coupled receptor on keratinocytes and may be activated by HDM to affect AD processes. We first established a HDM-derived AD mouse model in wild-type (WT) and Par2-/-mice. Single cell RNA sequencing of the diseased skins found a stronger cellular communication between the ligand macrophage migration inhibitory factor (MIF) from keratinocytes and its receptors on antigen-presenting cells, suggesting the critical role of MIF in AD. HDM-WT mice showed severer skin lesions and pathological changes with stronger immunofluorescence MIF signals in skin sections than HDM-Par2-/- mice. Primary keratinocytes from WT mice stimulated with HDM or SLIGRL (PAR2 agonist) secreted more MIF in cultured medium and induced stronger immunofluorescence MIF signals than those from Par2-/- mice. The skin section of HDM-WT mice showed higher immunofluorescence signals of P115 (relating to MIF secretion) and KIF13B (possibly relating to intracellular trafficking of MIF) than that of HDM-Par2-/- mice. Acetylation of α-tubulin increased after stimulation by SLIGRL in WT keratinocytes but not in Par2-/- keratinocytes. HDM-WT mice treated with the MIF antagonist ISO-1 displayed improvement of AD-like presentations and lower expressions of IL-4, IL-13, TSLP and Arg1 (a biomarker of M2 macrophage) mRNAs. We conclude that MIF is an important cytokine and is significantly increased in the AD model. PAR2 affects AD changes by regulating the expression, intracellular trafficking, and secretion of MIF in epidermis.